What are the Misconceptions that occur to Students in Science Learning in Indonesia? A Systematic Literature Review - Muhammad Ikhsan; Heru Kuswanto; Sri Atun; Naffa Afkarina Izzata Dini; Oky Pamungkas (UIN Fatmawati Sukarno Bengkulu, 2025)
This study is a systematic review of 26 articles published between 2017 and 2024, focusing on misconceptions in science education within Indonesian schools. Misconceptions, defined as persistent misunderstandings that hinder effective learning, are a significant barrier to students' scientific literacy. The research employs the Systematic Literature Review (SLR) method, following the PRISMA model, to synthesize findings and address key research questions regarding these misconceptions.The analysis reveals that the majority of misconceptions were identified in 2023, accounting for 27% of the total findings, with a notable prevalence at the high school level (50%), followed by junior high (31%) and elementary schools (19%). In terms of subjects, physics misconceptions dominate at 50%, followed by chemistry (31%) and biology (19%). Geographically, East Java emerges as a hotspot for these misconceptions, representing 27% of the cases analyzed.This research contributes to the field of science education by highlighting critical areas where misconceptions occur, particularly in physics at the high school level. By identifying these misconceptions, educators can develop targeted interventions to enhance teaching strategies and improve overall student comprehension in science, ultimately fostering better scientific literacy among Indonesian students.